2018
DOI: 10.1038/s41598-018-29612-2
|View full text |Cite
|
Sign up to set email alerts
|

Periostin as a novel biomarker for postoperative recurrence of chronic rhinosinitis with nasal polyps

Abstract: We previously reported that chronic rhinosinusitis with nasal polyps (CRSwNP) was subdivided into four chronic rhinosinusitis (CRS) subtypes using the JESREC scoring system. We sought to identify the gene expression profile and biomarkers related with CRSwNP by RNA-sequence. RNA-sequencing was performed to identify differentially expressed genes between nasal polyps (NPs) and inferior turbinate mucosa from 6 patients with CRSwNP, and subsequently, quantitative real-time PCR was performed to verify the results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 55 publications
3
90
0
Order By: Relevance
“…39,40 Reportedly, periostin levels were increased in ECRS, and cystatin SN stimulation increased periostin expression in cultured fibroblasts isolated from NPs. 36,41 These results further reinforce the possible role of cystatin SN in eosinophilic inflammation (Fig 2). According to a report from China, cystatin SN promotes the activation and recruitment of eosinophils through IL-5 induction, further supporting this hypothesis.…”
Section: Establishment Of Type 2 Inflammation In Ecrssupporting
confidence: 80%
“…39,40 Reportedly, periostin levels were increased in ECRS, and cystatin SN stimulation increased periostin expression in cultured fibroblasts isolated from NPs. 36,41 These results further reinforce the possible role of cystatin SN in eosinophilic inflammation (Fig 2). According to a report from China, cystatin SN promotes the activation and recruitment of eosinophils through IL-5 induction, further supporting this hypothesis.…”
Section: Establishment Of Type 2 Inflammation In Ecrssupporting
confidence: 80%
“…Overall, based on DEGs, 32 pathways (38%) overlap between the upper and lower airways, and 27 pathways were common to all three phenotypes (OM, CRS, and Lower; Supplementary Figure 5; Supplementary Table 5). Notably about half of these 27 pathways that were common in OM, CRS, and Lower also overlap with DEGs identified in previous microarray and RNA-Seq studies (Liu et al, 2004;Kwon et al, 2006;Lee et al, 2006;Payne et al, 2008;Raju et al, 2008;Stankovic et al, 2008;Rostkowska-Nadolska et al, 2011;Klenke et al, 2012;Macias et al, 2013;Wang et al, 2016;Ramakrishnan et al, 2017;Wang et al, 2017;Gao et al, 2018a;Gao et al, 2018b;Kato et al, 2018;Langelier et al, 2018;Ninomiya et al, 2018;Okada et al, 2018;Jovanovic et al, 2019;Walter et al, 2019;Yao et al, 2019). The common pathways from Part 2 RNA-Seq data that were identified in the transcriptome literature are apoptosis, cell adhesion, cell cycle, cell proliferation, chromatin organization/remodeling, Table 6).…”
Section: Genes and Pathways Identified By Rna-seq (Part 2)mentioning
confidence: 73%
“…Thus, the prognosis of CRS and prediction of recurrence are important factors, particularly if a patient is at increased risk of recurrence and a choice has to be made between surgical treatment or just controlling the symptoms with currently available medical treatment. To date, several methods have been described for predicting of the recurrence of CRS postsurgery, but these approaches are often invasive.…”
Section: Discussionmentioning
confidence: 99%
“…Lou and colleagues suggested that a tissue eosinophil proportion of >27% of total cells or a tissue eosinophil absolute count of >55 eosinophils per high‐power field may be reliable as markers for nasal polyp recurrence within 2 years after sinus surgery, whereas Younis and colleagues suggested that the presence of eosinophilic mucin was a strong predictor of CRS recurrence . Similarly, other studies suggested CRSwNP recurrence to be associated with occupational dust exposure, serum periostin, and polypoid change of anterior free border of middle turbinate . However, use of these markers is limited because they are either invasive or impossible to obtain before surgery.…”
mentioning
confidence: 99%